Using a Facebook Survey to Assess the Socioeconomic Conditions of Palestinians after the May 2021 Conflict : A Methodological Note - Aghajanian, Alia; Tao, Tao; Malasquez, Eduardo; Chatila, Mohamad; Afif, Zeina; De Castro Zoratto, Laura (World Bank, Washington, DC, 2022)
The World Bank launched the Rapid Web based Survey on the Impact of the Conflict (RWSIC) on June 9, 2021, covering key topics such as access to basic services, labor outcomes, mental health, and coping strategies. The survey was conducted over Facebook, using targeted advertisements based on gender, age and location to achieve a balance similar to the general population. 3,210 questionnaires were collected in over two weeks, providing much needed information on the living conditions of Palestinians. This study builds on the existing Facebook survey experience by targeting advertisements at a relatively local level and adjusting sampling weights based on the likelihood of the user seeing and responding to the survey’s advertisement before calibrating the weights to known parameters of the population. While this study offers some methods for alleviating the potential biases to representativeness, there could remain unobservable characteristics that make respondents systematically different to the rest of the population.